2022
DOI: 10.1016/j.intimp.2021.108502
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and inflammatory markers in patients with COVID-19: Potential role of RAGE, HMGB1, GFAP and COX-2 in disease severity

Abstract: Background SARS-CoV-2 infection can lead to the abnormal induction of cytokines and a dysregulated hyperinflammatory state that is implicated in disease severity and risk of death. There are several molecules present in blood associated with immune cellular response, inflammation, and oxidative stress that could be used as severity markers in respiratory viral infections such as COVID-19. However, there is a lack of clinical studies evaluating the role of oxidative stress-related molecules includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 73 publications
0
21
1
Order By: Relevance
“…The early involvement of the nervous system is well documented. [1,13] The neurological manifestations include encephalopathy, Guillain-Barré syndrome, acute disseminated encephalomyelitis, ischemic stroke, epilepsy and neuropathy as part of a broad spectrum that continues to be described. [13,[22][23][24] For a better understanding of how COVID-19 can impact nervous system and to validate candidate biomarkers for a practical approach of severity assessment, we enrolled 108 subjects from a 706-patient population admitted at the HUCFF ICU during the pandemics, between July 2020 and October 2021.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The early involvement of the nervous system is well documented. [1,13] The neurological manifestations include encephalopathy, Guillain-Barré syndrome, acute disseminated encephalomyelitis, ischemic stroke, epilepsy and neuropathy as part of a broad spectrum that continues to be described. [13,[22][23][24] For a better understanding of how COVID-19 can impact nervous system and to validate candidate biomarkers for a practical approach of severity assessment, we enrolled 108 subjects from a 706-patient population admitted at the HUCFF ICU during the pandemics, between July 2020 and October 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Also, they can act as potential tools for severity and mortality assessment during the acute infection. [11][12][13] NfL -a cytoskeletal intermediate lament protein of neurons -consists of an important biomarker of axonal damage and degeneration, strongly related to several neurological diseases, such as Multiple Sclerosis and Acute Disseminated Encephalomyelitis. [14].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with COVID-19 demonstrate post-infection upregulation of inflammatory biomarkers (49, 50) with the extent of the inflammatory response depending on disease severity (49, 50). Research among middle-aged COVID-19 survivors has shown significant inflammation-related astrocytic damage and neural dysfunction regardless of disease severity (51). Inflammation after COVID-19 infection may also impair cognition via reduced serotonin levels (52).…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 is an inducible enzyme, which usually exists at low levels in tissues but can be induced and produced in large quantities in the case of infection and injury. COX-2 is mainly expressed in neurons of cerebral cortex, hippocampus, amygdala, and spinal dorsal horn [ 12 ]. COX-2 expression was significantly increased in microglia and astrocytes under continuous neuroinflammatory response [ 13 ].…”
Section: Discussionmentioning
confidence: 99%